The Nursing Problem for Physical Mobility Impairments in Tibia Fracture Patients Post ORIF Operation with Rom Free Active Exercise (FAE) - I Gusti Ayu Ari Rasdini; I Made Mertha; Ni Made Wedri; I Wayan Sukawana; Lina Adhiutami (KHD-Production, 2024)
Open fracture of the tibia is a complex injury with multifactorial outcomes and variable prognosis. This final scientific work by nurses aims to determine nursing care for physical mobility disorders with range of motion free active exercise in post-ORIF surgery tibia fracture patients. This scientific work uses a descriptive method with a case study approach which was carried out on 30 October – 02 November 2023. The results of the study showed data that the patient said he had pain in his left leg, did not dare to move his left leg, the back of his left leg was swollen. The nursing diagnosis of impaired physical mobility is related to pain. Nursing interventions are ambulation support, mobilization support and pain management with the criteria of increasing physical mobility. Innovation intervention range of motion free active exercise with 2 times the frequency of 2x8 steps. The nursing evaluation showed that physical mobility problems had decreased. Conclusion: range of motion free active exercise can increase range of motion, increase muscle strength, reduce complaints of pain, reduce anxiety when moving, and reduce edema. Suggestions for health workers can apply the results of non-pharmacological therapy research, especially range of motion free active exercise, to treat post-operative patients with complaints of physical mobility problems.